1997
DOI: 10.1007/s004420050204
|View full text |Cite
|
Sign up to set email alerts
|

Between-tree variations in leaf ? 13 C of Quercus pubescens and Quercus ilex among Mediterranean habitats with different water availability

Abstract: In this study, sun leaf carbon isotope composition (δC) of two co-occurring woody Mediterranean species (Quercus pubescens Willd., a deciduous oak, and Q. ilex L., an evergreen one) was investigated on four sites with different water availability. The total range of δC values was 4.4 and 3.1‰ for Q. pubescens and Q. ilex respectively. The intra-site variability was about 3‰. Total mean per species was equal. There were significant differences among sites, but at each site means of δC were not significantly dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
73
3
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 43 publications
9
73
3
1
Order By: Relevance
“…Many other studies have found positive correlations for woody species between D and indices of water availability such as rainfall, transpiration, soil water potential, predawn leaf water potential and soil water availability, and negative correlations between D and either potential evaporation or global solar radiation (Leavitt & Long 1991;McNulty & Swank 1995;Stewart et al 1995;Damesin, Rambal & Joffre 1997;Walcroft et al 1997;Schulze et al 1998;Korol et al 1999;Anderson et al 2000;Miller et al 2001;Barbour et al 2002). However, our study is one of few to have also quantified productivity, leaf traits and their relation to D in a similar genotype across a large gradient of water availability.…”
Section: Discussionmentioning
confidence: 73%
“…Many other studies have found positive correlations for woody species between D and indices of water availability such as rainfall, transpiration, soil water potential, predawn leaf water potential and soil water availability, and negative correlations between D and either potential evaporation or global solar radiation (Leavitt & Long 1991;McNulty & Swank 1995;Stewart et al 1995;Damesin, Rambal & Joffre 1997;Walcroft et al 1997;Schulze et al 1998;Korol et al 1999;Anderson et al 2000;Miller et al 2001;Barbour et al 2002). However, our study is one of few to have also quantified productivity, leaf traits and their relation to D in a similar genotype across a large gradient of water availability.…”
Section: Discussionmentioning
confidence: 73%
“…For pubescens [14]. These ranges are much greater than those normally found within natural ecosystems, but are less than those recorded by Mooney et al [45] and Kohom et al [39].…”
mentioning
confidence: 59%
“…Thus greater leaf nitrogen contents would bring about comparatively larger stomatal conductances, with increased intercellular CO 2 concentrations and leaf carbon isotope discrimination. Other studies, such as that of Damesin, Rambal & Joffre (1997), found no correlation between leaf ∆ 13 C and the massbased nitrogen content in leaves of two oak species occurring in sites with different water availability.…”
mentioning
confidence: 74%